Halal Food Industry Development Strategy in Increasing Medan Community Consumption Activities - Ahmad Kurnia; Marliyah Marliyah; Juliana Nasution; Maryam Batubara (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to find out how the main priority strategy for the development of the Halal Food Industry is to increase the consumption activities of the people of Medan City by presenting the internal and external conditions that have been carried out so far. Then in addition, the researcher also explained several handling urgency that needed to be implemented so that the development of the Halal Food Industry could be more focused. The method used is a qualitative method using SWOT analysis and QSPM. The number of respondents who filled out the questionnaire was 5 respondents from SMEs in Medan City and 5 respondents from experts. Based on the results of the SWOT analysis, the strategy quadrants obtained after being processed in the IFE and EFE matrices are in Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy means that the Halal Food industry has strengths and opportunities. Furthermore, in the QSPM analysis, the results show that the main priority strategy that must be carried out is Utilizing Halal Product Companion Training so that the Halal Industry has the opportunity to enter the Global Market.